Influence of Mechanical Deformations of HTSC Tapes on the Current-Carrying Characteristics in the Creation of a CORC Cable - Veselova, S. V.; Abin, D. A.; Starikovskii, A. S.; Pokrovskii, S. V.; Rudnev, I. A.; Novikov, M. S. (Physics of atomic nuclei, 2022)
High-temperature superconducting magnets are a system with a complex configuration. In the process of creating such systems, HTSC tapes can be subject to mechanical damage, which leads to a deterioration in the transport characteristics of the tape. This paper presents the results of experimental studies of the effect of mechanical stresses on the transport characteristics of the second-generation HTSC tapes. The volt-ampere characteristics of various samples of second-generation HTSC tapes were measured during their winding on cylindrical formers of various diameters. Winding was carried out at the angles of 22° and 40° relative to the former axis with a force from 10 to 20 N. Different winding options were compared and the optimal set of winding configurations corresponding to the minimum degradation of the critical current of the tape was determined. Scanning Hall magnetometry is used to determine the regions of localization of defects arising at various winding options. All measurements were carried out at the boiling point of liquid nitrogen. The obtained data made it possible to calculate the area of flow of the longitudinal and transverse components of the current in each individual case.